Differences in Selected HIV Care Continuum Outcomes Among People Residing in Rural, Urban, and Metropolitan Areas—28 US Jurisdictions. Issue 1 (13th September 2016) - Nelson, John A.; Kinder, Anna; Johnson, Anna Satcher; Hall, H. Irene; Hu, Xiaohong; Sweet, Donna; Guido, Alyssa; Katner, Harold; Janelle, Jennifer; Gonzalez, Maribel; Paz, Natalia Martínez; Ledonne, Charlotte; et al.
Abstract: Purpose: The HIV care continuum is used to monitor success in HIV diagnosis and treatment among persons living with HIV in the United States. Significant differences exist along the HIV care continuum between subpopulations of people living with HIV; however, differences that may exist between residents of rural and nonrural areas have not been reported. Methods: We analyzed the Centers for Disease Control and Prevention's National HIV Surveillance System data on adults and adolescents (≥13 years) with HIV diagnosed in 28 jurisdictions with complete reporting of HIV‐related lab results. Lab data were used to assess linkage to care (≥1 CD4 or viral load test ≤3 months of diagnosis), retention in care (≥2 CD4 and/or viral load tests ≥3 months apart), and viral suppression (viral load <200 copies/mL) among persons living with HIV. Residence at diagnosis was grouped into rural (<50, 000 population), urban (50, 000‐499, 999 population), and metropolitan (≥500, 000 population) categories for statistical comparison. Prevalence ratios and 95% CI were calculated to assess significant differences in linkage, retention, and viral suppression. Findings: Although greater linkage to care was found for rural residents (84.3%) compared to urban residents (83.3%) and metropolitan residents (81.9%), significantly lower levels of retention in care and viral suppression were found for residents of rural (46.2% and 50.0%, respectively) and urban (50.2% and 47.2%) areas compared to residents of metropolitan areas (54.5% and 50.8%). Conclusions: Interventions are needed to increase retention in care and viral suppression among people with HIV in nonmetropolitan areas of the United States.